Comprehensive Pan-Cancer Analysis Confirmed That ATG5 Promoted the Maintenance of Tumor Metabolism and the Occurrence of Tumor Immune Escape - Xu, Chunxiao; Zang, Yusheng; Zhao, Yuxiang; Cui, Weiqiang; Zhang, Hong; Zhu, Yingcui; Xu, Man (Frontiers in Oncology, 2021)
Background: Autophagy related protein 5 (ATG5) is an important autophagosome formation related protein, and its involvement in the biological process of autophagy has been shown to correlate with tumor metabolic patterns and the formation of tumor heterogeneity. However, the role of ATG5 in tumor metabolism and tumor immunity remains unclear. Method: In order to explore this problem, this study was designed to to reveal the role of ATG5 in tumor metabolism and tumor immunity through pan-cancer analysis of multi-database. GTEx database, CCLE database, and TCGA database were used to describe the expression, prognosis, immune microenvironment, immune new antigen, immune checkpoint, TMB, and microsatellite instability of ATG5 in 33 types of tumors. A series of bioinformatics tools and methods were used for quantitative analysis and panoramic description, such as to Estimate, Scanneo and GSEA. Result: The differential analysis results of multiple databases showed that ATG5 was ubiquitously highly expressed in pan-cancer, especially in solid tumors. Survival analysis revealed that ATG5 was universally associated with the prognosis of pan-cancer, and high ATG5 expression was significantly associated with poor patient prognosis in most cases. Further, the expression level of ATG5 was confirmed to be associated with tumor immune infiltration and tumor microenvironment, especially in BRCA, KIRC, and LIHC. In addition to this, ATG5 expression was confirmed to correlate with these clinically significant phenotypes, in conjunction with immune neoantigens and immune checkpoint gene expression profiles in pan-cancer. In addition to TMB and microsatellite instability in pan-cancer, we confirmed that ATG5 expression affects the expression of DNA repair genes and methyltransferases in pan-cancer, and found through gene set enrichment analysis that ATG5 is involved in the regulation of numerous signaling pathways involved in cancer metabolism and cancer immunity. Conclusions: In addition to LC3-II, an important molecule involved in autophagosomal membrane formation, ATG5 has also been shown to play an important role in tumor metabolism and tumor immunity. The comprehensive pan-cancer analysis not only revealed the potential of ATG5 in tumor-targeted therapy but also suggested ATG5 as a promising tumor predictive biomarker in most solid tumors.